Strategi Pencegahan Penipuan Identitas Kependudukan Digital (IKD) yang Mengatasnamakan Dispenduk - Ningrum, Putri Puspita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research discusses strategies to prevent Digital Population Identity (IKD) fraud on behalf of the Population Office (Dispenduk) in Indonesia. With the advancement of information technology, the digitalization of public services through IKD aims to facilitate access to administrative services. However, there is a threat of digital fraud carried out by individuals pretending to be official officers, asking for citizens' personal data. This research uses a qualitative approach with a case study method, involving interviews with victimized residents and village officials. The results show that community digital literacy is crucial in preventing fraud. Proposed prevention strategies include socialization, education, and collaboration with the police. This research is expected to serve as a foundation for further studies on personal data security in digital administrative services.